Strategic management a stakeholder approach - Freeman, R. Edward 1951- (Cambridge University Press, 2010)
Strategic Management: A Stakeholder Approach was first published in 1984 as a part of the Pitman series in Business and Public Policy. Its publication proved to be a landmark moment in the development of stakeholder theory. Widely acknowledged as a world leader in business ethics and strategic management, R. Edward Freeman's foundational work continues to inspire scholars and students concerned with a more practical view of how business and capitalism actually work. Business can be understood as a system of how we create value for stakeholders. This worldview connects business and capitalism with ethics once and for all. On the 25th anniversary of publication, Cambridge University Press are delighted to be able to offer a new print-on-demand edition of his work to a new generation of readers